Europejski rynek wewnętrzny 1992 roku i jego implikacje dla Polski - Komar, Andrzej (Wydział Prawa i Administracji UAM, 1989)
The article discusses the process of formation of internal makret of 12 member states of the European Communities and analyses its implications for Poland. Attention was paid to the fact that European internal market is a consequence of economic integration within the Communities. In June 1985 the Commission prepared for the Council of Ministers the so-called White Paper on the implementation of internal market. Its content is very interesting, for it defines the features of internal market and contains about 300 proposals to implement internal market in various spheres. These proposals are accompanied by a detailed schedule of their realization. By the end of 1988 the Council of Ministers took about 90 decisions with respect to the internal market implementation; further steps are being discussed in working groups. The White Paper was later confirmed by Single European Acts, having the binding force of treaties. Single European Acts define the notion of internal market of member states of the Communities, proclaim the rule of qualified majority vote for decisions taken by the Council and set the deadline for a full realization of internal market for December 31, 1992. Various economic implications for Poland result from the above. It is indispensable for Polish economy to achieve a certain degree of convergence with the economies of member states of the Communities. In order to accomplish it, deep reforms of the structure of economy and management are necessary. The article indicates main directions of reforms and ways of carrying them out. It is a very demanding task for the Polish economic policy. Otherwise, Poland would find itself outside the economic relations with the Communities. Therefore, the article is against „emergency" reforms and instead postulates the realization of far-reaching reforms which would take into account the changes on the economic map of Europe.
European Internal Market of 1992 and its implications for Poland